2011
DOI: 10.1007/s00415-011-6147-1
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia, thalamus and neocortical atrophy predicting slowed cognitive processing in multiple sclerosis

Abstract: Information-processing speed (IPS) slowing is a primary cognitive deficit in multiple sclerosis (MS). Basal ganglia, thalamus and neocortex are thought to have a key role for efficient information-processing, yet the specific relative contribution of these structures for MS-related IPS impairment is poorly understood. To determine if basal ganglia and thalamus atrophy independently contribute to visual and auditory IPS impairment in MS, after controlling for the influence of neocortical volume, we enrolled 86 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
221
3
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(260 citation statements)
references
References 33 publications
28
221
3
8
Order By: Relevance
“…28 Normalized SDGM volumes were thus obtained by multiplying the estimated volumes from FIRST by the volumetric scaling factor from SIENAX. 29 Reproducibility of FIRST was previously reported.…”
Section: Mr Imaging Methodsmentioning
confidence: 83%
“…28 Normalized SDGM volumes were thus obtained by multiplying the estimated volumes from FIRST by the volumetric scaling factor from SIENAX. 29 Reproducibility of FIRST was previously reported.…”
Section: Mr Imaging Methodsmentioning
confidence: 83%
“…The range of specific cognitive deficits, such as memory disorders, reduced processing speed, and attention disorders, can be better explained by the cortical gray matter lesions (lesions and atrophy) than subcortical white matter lesions [25]. It has been shown that neocortical atrophy is associated with impaired verbal memory, visual episodic and working memory, verbal fluency, attention/concentration, and processing speed [26]. It is also possible that the neocortical atrophy is further responsible for slight personality changes, such as euphoria, that are seen in MS patients [27].…”
Section: Cognitive Abilities and Imaging Methodsmentioning
confidence: 99%
“…23 The reproducibility of FIRST has been previously reported. 37 Examples of subcortical segmentation of a subject classified as having PD-MCI and of a subject classified as having PD-NCI are presented in Fig 1. In subsequent volumetric analyses, the normalization factor from SIENAX was included to reduce the effects of interindividual variability due to head size. 34 Vertex Analysis for Assessment of SDGM Shape Alterations.…”
Section: Image Analysismentioning
confidence: 99%